An Injectable Hydrogel to Modulate T Cells for Cancer Immunotherapy. Issue 32 (17th July 2022) - Zhang, Di; Li, Qian; Chen, Xiangwu; Nie, Xinxin; Xue, Fumin; Xu, Wei; Luan, Yuxia
Abstract: T cell exhaustion caused by mitochondrial dysfunction is the major obstacle of T cells‐based cancer immunotherapy. Besides exhausted T cells, the insufficient major histocompatibility complex class I (MHC I) on tumor cells leads to inefficient T cell recognition of tumor cells, compromising therapeutic efficacy. Therapeutic platform to regulate T cell exhaustion and MHC I expression for boosting T cells‐based cancer immunotherapy has not been realized up to date. Herein, an injectable hydrogel is designed to simultaneously tune T cell exhaustion and MHC I expression for amplified cancer immunotherapy. The hydrogel is in situ constructed in tumor site by utilizing oxidized sodium alginate‐modified tumor cell membrane vesicle (O‐TMV) as a gelator, where axitinib is encapsulated in the lipid bilayer of O‐TMV while 4‐1BB antibody and proprotein convertase subtilisin/kexin type 9 inhibitor PF‐06446846 nanoparticles are present in the cavities of hydrogel. After immune response trigged by O‐TMV antigen, the 4‐1BB antibody‐promoted T cell mitochondrial biogenesis and the axitinib‐lowered hypoxia synergistically reverse T cell exhaustion while the PF‐06446846‐amplified MHC I expression facilitates T cell recognition of tumor cells, demonstrating a powerful immunotherapeutic efficacy. This strategy on reprograming T cell exhaustion and improving T cell potency offers new concept for T cells‐based cancer immunotherapy. Abstract : An injectable hydrogel is designed to reprogram T cell exhaustion and amplify specific T cell recognition of tumor cells for boosting T cells‐based cancer immunotherapy, demonstrating powerful suppression of tumor growth, metastasis, and recurrence via the induced strong systemic and long‐term memory immune response. This study offers new concept for T cells‐based cancer immunotherapy.